Depths and temperatures of <10.5 Ma mantle melting and the lithosphere‐asthenosphere boundary below southern Oregon and northern California. (17th April 2013) - Till, Christy B.; Grove, Timothy L.; Carlson, Richard W.; Donnelly‐Nolan, Julie M.; Fouch, Matthew J.; Wagner, Lara S.; Hart, William K.
Abstract: [1] Plagioclase and spinel lherzolite thermometry and barometry are applied to an extensive geochemical dataset of young (<10.5 Ma) primitive basaltic lavas from across Oregon's High Lava Plains, California's Modoc Plateau, and the central‐southern Cascades volcanic arc to calculate the depths and temperatures of mantle melting. This study focuses on basalts with low pre‐eruptive H2 O contents that are little fractionated near‐primary melts of mantle peridotite (i.e., basalts thought to be products of anhydrous decompression mantle melting). Calculated minimum depths of nominally anhydrous melt extraction are 40–58 km below Oregon's High Lava Plains, 41–51 km below the Modoc Plateau, and 37–60 km below the central and southern Cascades arc. The calculated depths are very close to Moho depths as determined from a number of regional geophysical studies and suggest that the geophysical Moho and lithosphere‐asthenosphere boundary in this region are located in very close proximity to one another (within 5–10 km). The basalts originated at 1185–1383°C and point to a generally warm mantle beneath this area but not one hot enough to obviously require a plume contribution. Our results, combined with a range of other geologic, geophysical, and geochemical constraints, are consistent with a regional model whereby anhydrous mantle melting over the last 10.5 Ma in a modern convergent margin and back arc was driven by subduction‐induced corner flow in the mantle wedge, and to a lesser extent, toroidal flow around the southern edge of the subducting Juan de Fuca and Gorda plates, and crustal extension‐related upwelling of the shallow mantle. Key Points: <10.5 Ma basalts are from 37–60 km depth and 1185–1383°C The Moho and lithosphere‐asthenosphere boundary are located very close to one another (5–10 km) in this region Anhydrous mantle melting is driven by subduction‐related mantle flow